Review on techniques of automatic solid waste separation in domestic applications - Luisa María Alcaraz-Londoño; Luis Felipe Ortiz-Clavijo; Carlos Julián Gallego Duque; Sergio Armando Gutiérrez Betancur (Institute of Advanced Engineering and Science, 2022)
The accelerated modern day urban development is accompanied by an increasing production of solid waste. While managing solid waste on an industrial scale presents different technological challenges, managing household waste requires decentralized solutions dealing with the associated logistic and technical difficulties. In this review, we identify the research trends on household waste recycling by providing a brief description of the main technologies, and the traditional formats commonly used for solid waste (SW) separation. We identify two main threads: the SW management systems within a smart city framework and the design of domestic waste classification systems based on intelligent mechanisms tailored to user psychology. Among the main conclusions, we verify a growing interest in the subject of SW separation in domestic applications, mainly through solutions based on automation and internet of things (IoT). Also, we detected a increasing interest in the analysis of psychological aspects and in citizen education in relation to the importance of recycling, since without this notion the success of proposed solutions might be limited.